2022
DOI: 10.1177/20570473221106025
|View full text |Cite
|
Sign up to set email alerts
|

The internal dynamics of “scaling up” deliberative mini-publics

Abstract: Recent deliberative systems research has emphasized the need to “scale up” deliberative mini-publics by exploring connections between mini-publics and broader arenas of policymaking. Less is known, however, about how the policy environment in a state or region might itself influence a deliberative event. In this article, we set out to examine how the internal dynamics of mini-publics are affected by the scaling-up process of connecting to larger policymaking domains. To better understand how the external role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The group, therefore, decided to report a mix of convergent and divergent opinions in their final votum. While many citizens did not perceive this lack of a full consensus as a problem but rather as a result of a pluralistic view on a complex topic, some interviewees showed signs of a pragmatic orientation (Rountree et al, 2022): “ the approach to incorporate every opinion made things endless and watered down the votum ” (Int.CP). Here another, observed and often mentioned criticism comes into play: many citizens felt that there was “ too little time between expert-hearing and then processing the new information and the [formation of the final votum] the following Sunday ” (Int.CP).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The group, therefore, decided to report a mix of convergent and divergent opinions in their final votum. While many citizens did not perceive this lack of a full consensus as a problem but rather as a result of a pluralistic view on a complex topic, some interviewees showed signs of a pragmatic orientation (Rountree et al, 2022): “ the approach to incorporate every opinion made things endless and watered down the votum ” (Int.CP). Here another, observed and often mentioned criticism comes into play: many citizens felt that there was “ too little time between expert-hearing and then processing the new information and the [formation of the final votum] the following Sunday ” (Int.CP).…”
Section: Resultsmentioning
confidence: 99%
“…However, inherent challenges, for example regarding unequally distributed abilities to engage in rational discourse, or finding consensus within increasingly contested context remained (Van Bouwel & van Oudheusden, 2017). While some authors urge organizers of deliberation events to remain open for all potential context (Richter et al, 2022; Rountree et al, 2022), a number of interviewees showed a “pragmatic orientation” (Rountree et al, 2022) arguing that the wide scope of the event coupled with a tight time schedule contributed to an output that they saw as too vague and diverse to have an impact on policy making. Instead, like in many previous studies, the main impact was perceived to be on individual learning around genome editing and citizen participation (Dryzek & Tucker, 2008; Guston, 1999; Rask & Worthington, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations